Hollow bulb obturator in right total maxillectomy patient (Bangladesh Journal of Medical Science, 2014)
Maxillectomy is relatively a common surgical procedure, resulting in a surgical defect. The acquired defect needs to be corrected by the prosthetic replacement, challenging the goals of prosthodontic treatment which includes special clinical and lab procedure for the fabrication of obturator for a patient who has undergone maxillectomy. This article describes the stepwise procedure for the fabrication of hollow bulb obturator. DOI: http://dx.doi.org/10.3329/bjms.v14i1.16988 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.91-94